Anchoring on Historical Round Number Reference Points: Evidence from Durable Goods Resale Prices - Wiltermuth, Scott S.; Gubler, Timothy; Pierce, Lamar (Organization Science, 2023)
This paper examines how people price the resale of durable goods in systematically biased ways. We show across four studies that the anchoring effect of durable goods’ prior sales prices on subsequent valuations is discontinuous at psychologically salient round number reference points (e.g., $10,000 increments) because these numbers create qualitative differences in how people perceive values below them versus values at/above them. Resellers set disproportionately larger subsequent prices when previous prices move from just below round number thresholds (e.g., $349,000) to those at or just above these thresholds (e.g., $351,000). The findings show that buyers who pay a price just below a round number, therefore, may sacrifice money because they receive disproportionately less when reselling the good. Market forces only partially attenuate this pricing bias, but valuator experience seems to play a moderating role. Archival data show that home buyers who previously paid just under a $10,000 reference point subsequently listed their homes for about 1.8% (over $3,700) less on average than did buyers selling comparable homes who previously paid at or above a round number threshold. This drop is observable controlling for home characteristics and the general relationship between previous and current prices. Three experimental studies looking at housing and used car markets replicate these findings, highlight the mechanism, and increase confidence in causality. Market mechanisms and the negotiation process attenuate discontinuities by about 30%, but lower initial listing prices persist to final sales prices. We find additional weak evidence suggesting that valuator experience may attenuate intergenerational pricing bias. Conflict of Interest: This manuscript was submitted, revised, and accepted prior to the nomination and appointment of Lamar Pierce as Editor-in-Chief. Funding: This project was supported by the University of Southern California Marshall School of Business Behavioral Laboratory. Supplemental Material: The online appendix is available at https://doi.org/10.1287/orsc.2022.1632 .